Bailey's Industrial Oil and Fat Products 2005
DOI: 10.1002/047167849x.bio012
|View full text |Cite
|
Sign up to set email alerts
|

Minor Components of Fats and Oils

Abstract: Vegetable oils contain a wide range of minor components besides triacylglycerols, the major components of most oils. Sterols, tocopherols, carotenoids, phenolic compounds, chlorophyll, free fatty acids, and other minor derivatives, as well as trace metal ions are the most recognized of these compounds. Minor lipid components are of interest because they affect the technical properties of the oil, possibly provide health benefits, and/or might be used for the authentication of different oils and their mixtures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 267 publications
0
14
0
1
Order By: Relevance
“…Phytosterols are compounds of great nutritional relevance in vegetable oils (Kamal‐Eldin, 2005). Accordingly, breeding for increasing their levels in oilseeds is an important objective for producing healthier oils as well as for the valorization of byproducts of the oil industry, as up to 70% of the seed phytosterols may be retained during the oil refining process (Kochhar, 1983).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytosterols are compounds of great nutritional relevance in vegetable oils (Kamal‐Eldin, 2005). Accordingly, breeding for increasing their levels in oilseeds is an important objective for producing healthier oils as well as for the valorization of byproducts of the oil industry, as up to 70% of the seed phytosterols may be retained during the oil refining process (Kochhar, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Fernández‐Cuesta et al (2012b) found a kernel phytosterol content between 2179 and 3555 mg kg −1 seed kernel in confectionery sunflower landraces. After oil extraction, phytosterols are generally the predominant compounds in the unsaponifiable fractions of vegetable oils (Kamal‐Eldin, 2005). Vlahakis and Hazebroek (2000) reported phytosterol content between 2100 and 4540 mg kg −1 in the seed oil of 12 sunflower cultivars.…”
mentioning
confidence: 99%
“…Minor components (less than 5%) are also present in vegetable oils, such as glycerolipids, phospholipids, and non-glycerolipids, including sterols, tocopherols/tocotrienols, free fatty acids, vitamins, pigments, proteins and phenolic compounds [ 71 , 72 ]. Most of these minor components have a polar character [ 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to triglycerides, the presence of minor components (less than 5%) in vegetable oils ( Figure 2 ) cannot be ignored due to their interesting biological properties and nutritional values for pharmaceutical and nutraceutical industries, particularly in virgin oils [ 10 , 11 ]. They can be divided into two types: glycerolipids such as mono- and diglycerides, phospholipids, and non-glycerolipids including sterols, tocopherols/tocotrienols, free fatty acids, vitamins, pigments, proteins, phenolic compounds, water, etc.…”
Section: Vegetable Oils Are Not Only Triglyceridesmentioning
confidence: 99%
“…depending on the oil type [ 22 ]. Phytosterols are affected by several oil refining processes, in which deodorization can significantly reduce the total sterols due to distillations and esterifications of free sterols [ 11 ]. Since phytosterols are rather hydrophobic and poorly soluble in fats, they are usually esterified to make them liposoluble for easily processing handling in the food industries [ 23 ].…”
Section: Vegetable Oils Are Not Only Triglyceridesmentioning
confidence: 99%